Conquering a new domain: Explaining great power competition in cyberspace - Domingo, Francis Rico C. (Animo Repository, 2016)
This article explains why powerful states develop capabilities for warfare in cyberspace. It argues that despite the apparent limited strategic utility of cyberspace, powerful states develop cyber capabilities to compete for military dominance in the international system. This argument is best explored using a neorealist framework because it provides the most compelling explanation for the competitive behavior of states in cyberspace. Three key implications can be derived from the study: the proliferation of capabilities for warfare in cyberspace is inevitable; powerful states will still dominate cyberspace; and cyberattacks may escalate to kinetic attacks due to the uncertainties regarding existing cyber capabilities.